Biomechanics of coaching maximal instep soccer kick for practitioners - Shan, G.; Zhang, X.; Wan, B.; Yu, D.; Wilde, B.; Visentin, P. (Interdisciplinary Science Reviews, 2019)
Kicking in soccer has been the subject of scientific research for more than 40 years yet review articles summarizing the biomechanical fundamentals of kick optimization as a guide to coaching are scarcely to be found. The current review article aims to bridge the gap between scientific research into the maximal instep kick (including studies employing 3D motion capture and full-body biomechanical modelling) and the application of such research in coaching. It does so by supplying a scientifically founded, coaching-friendly article explaining identifiable characteristics and motor control sequencing that define this skill. Relevant biomechanical factors are identified in a way that should help coaches better develop training programmes and, at the same time, foster better understanding of the skill among athletes. Such information will contribute to both accelerated skill acquisition and, by concomitant gains in skill efficiency, the development of programmes that minimize risk of injury to athletes during training.